Improvement of Snap Beans Yield through the Application of N, P, K and Granule Organic Fertilizers on Inceptisols Soil - Kusumiyati; Sutari, Wawan; Affan Wicaksono, Arif; Risti Oktavia, Ade (Jurnal Hortikultura Indonesia (JHI), 2020)
Balanced organic and inorganic fertilization is expected to improve low nutrient on Inceptisols to increased snap bean production. The effect of the combination of N, P, K, and granule organic fertilizer on bean harvests was the purpose of this study. The parameters were leaf area index (LDA), shoot-root ratio, the weight of pods, pod length, pod diameter, percentage of the number of pods, marketable and unmarketable,and percentage of pods by quality class. The experiment was conducted in February to April 2016 at Ciparanje Experimental Farm, Faculty of Agriculture, Padjadjaran Univeristy, Jatinangor. The study was conducted using a randomized block design (RBD) with 10 treatments and 3 replications. The experimental results showed that N, P, K fertilizer and granule organic fertilizer (GOF) in the order of Inceptisols significantly affected the weight of pods. Application 50% of the dosage N, P, K fertilizer combined with 50% dosage of granule organic fertilizer resulted in a higher pod weight per plot, which reached 2 439.84 g. Keywords: an organic fertilizer, granule organic fertilizer, leaf area index, quality grade, shoot-root ratio,